Update of Research Progress on Small Incision Lenticule Extraction (SMILE) Lenticule Reuse - Zhang H; Deng Y; Li Z; Tang J (Clinical Ophthalmology, 2023)
Hao Zhang,1 Yingping Deng,1 Zeshi Li,2 Jing Tang1 1Department of Ophthalmology, West China Hospital, Sichuan University, Chengdu, Sichuan, People’s Republic of China; 2West China Clinical Medical College, Sichuan University, Chengdu, Sichuan, People’s Republic of ChinaCorrespondence: Jing Tang, Email tangjing0802@163.comAbstract: The SMILE lenticule is a complete corneal stroma that is removed from SMILE surgery. Since the increasing number of SMILE surgeries, a large number of SMILE lenticules have been produced, so the reuse and preservation of the stromal lens has become a research hotspot. Due to the rapid development of the preservation and clinical reuse of SMILE lenticules, there have been many related studies in recent years, so we updated it on this basis. We searched PubMed, Web of Science, Embase, Elsevier Science, CNKI, WANFANG Data and other databases for all articles published on the preservation and clinical reuse of SMILE lenticules, screened useful articles, selected relevant articles published in the last five years as the main body for summary, and then reached a conclusion. The existing preservation methods of SMILE lenticule include Moist chamber storage at low temperature, cryopreservation technique dehydrating agent and corneal storage medium, which have their own advantages and disadvantages. Presently, smile lenticules can be used for the treatment of corneal ulcers and perforations, corneal tissue defects, hyperopia, presbyopia and keratectasia, which have been proven to be relatively effective and safe. More research on smile lenticule reuse needs to be carried out to confirm its long-term efficacy.Keywords: SMILE lenticule, refractive surgery, preservation, clinical reuse